Tuning Pt and Cu sites population inside functionalized UiO-67 MOF by controlling activation conditions. (16th June 2017) - Braglia, L.; Borfecchia, E.; Lomachenko, K. A.; Bugaev, A. L.; Guda, A. A.; Soldatov, A. V.; Bleken, B. T. L.; Øien-Ødegaard, S.; Olsbye, U.; Lillerud, K. P.; Bordiga, S.; Agostini, G.; et al.
Abstract : The exceptional thermal and chemical stability of the UiO-66, -67 and -68 classes of isostructural MOFs [ J. Am. Chem. Soc., 2008, 130, 13850] makes them ideal materials for functionalization purposes aimed at introducing active centres for potential application in heterogeneous catalysis. We previously demonstrated that a small fraction (up to 10%) of the linkers in the UiO-67 MOF can be replaced by bipyridine-dicarboxylate (bpydc) moieties exhibiting metal-chelating ability and enabling the grafting of Pt(ii ) and Pt(iv ) ions in the MOF framework [ Chem. Mater., 2015, 27, 1042] upon interaction with PtCl2 or PtCl4 precursors. Herein we extend this functionalization approach in two directions. First, we show that by controlling the activation of the UiO-67-Pt we can move from a material hosting isolated Pt(ii ) sites anchored to the MOF framework with Pt(ii ) exhibiting two coordination vacancies (potentially interesting for C–H bond activation) to the formation of very small Pt nanoparticles hosted inside the MOF cavities (potentially interesting for hydrogenation reactions). The second direction consists of the extension of the approach to the insertion of Cu(ii ), obtained via interaction with CuCl2, and exhibiting interesting redox properties. All materials have been characterized by in situ X-ray absorption spectroscopy at the Pt L3 - and Cu K-edges.